Design, Synthesis and In vitro Screening of Novel 2-Mercaptobenzothiazole- Clubbed Phenylacetamides as Potential Antibacterial Agents - Gurram, Swarupa R.; Azam, Mohammed Afzal; Palathoti, Nagarjuna (Letters in Drug Design & Discovery, 2024)
Background: The frightening rise of bacterial resistance is occurring worldwide and endangering the efficacy of antibiotics. Hence, the development of novel and potent antibacterial is a need of the day. Objective: In this study, we designed and synthesized compounds C1-C11. These compounds are characterized by their FT-IR, NMR and MS spectral data and examined in vitro for their antibacterial activity. Methods: Compounds C1-C11 were synthesized by reacting 2-mercaptobenzothiazole with appropriate chloroacetamide in the presence of anhydrous potassium carbonate and dry acetone at room temperature. To assess the antibacterial activity, minimum inhibitory and minimum bactericidal concentrations were examined by broth microdilution method against the selected strains of both Gram-positive and Gramnegative bacteria. Time-kill kinetics study was also performed as per CLSI guidelines. Results: Compounds C6 and C7 displayed promising activity against Staphylococcus aureus ATCC 43300 with MICs of 9.43 and 7.73 μM, respectively. These two compounds also displayed promising antibacterial activity against S. aureus 5021 with MIC values of 7.53 and 9.68 μM, respectively. In MBC determination, these two compounds (tested in the concentration range of 7.53 to 262.3 μM) displayed bactericidal activity against methicillin resistant S. aureus ATCC 43300, S. aureus NCIM 5021 and S. aureus NCIM 5022. In time-kill kinetics study, compounds C6 and C7 also exhibited bactericidal activity against S. aureus NCIM 5021 and S. aureus ATCC 43300 after 12 h of exposure. In general, all tested compounds exhibited poor activity against Mycobacterium sp. NCIM 2984 and also against tested Gramnegative bacteria Klebsiella pneumoniae NCIM 2706, Escherichia coli NCIM 2065 and Pseudomonas aeruginosa NCIM 2036. Further, computed ADMET properties of C1-C11 showed a favourable pharmacokinetic profile with zero violation of Lipinski's rule of five. Conclusion: The result showed that in phenylacetamides C6 and C7 presence of phenyl ring substituted with -CF3 group is responsible for their high antibacterial activity against S. aureus ATCC 43300 (MICs, 9.43 and 7.73 μM, respectively). These two compounds also exhibited bactericidal activity respectively against S. aureus NCIM 5021 in time kill kinetics study.
Keywords: heterocyclic skeletons